Working at relational depth in counselling and psychotherapy - Mearns, Dave.; Cooper, Mick (Chartered counselling psychologist) (London : SAGE, 2005)
Going to the very heart of the therapeutic meeting between therapist and client, this text explains the concept of 'relational depth', in which both therapist and client experience profound feelings of contact and engagement with each other.
Includes bibliographical references (p. 165-174) and index.
Keywords: Psychotherapist and patient; Psychotherapy; Health and Wellbeing